URBAN ACUPUNCTURE : INVESTIGASI POLA PERILAKU TERHADAP STREET FURNITURE DI RUANG PUBLIK KAMPUS - Dominikus Aditya Fitriyanto; Fairuz Mutia; Aloysia Krisnawatie (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: The era of the pandemic, which is currently starting to move to endemic has resulted in the flow of density of teaching and learning activities on campus. Some students started doing offline practicums, and also guidance activities for lecturers in the lecture building, of course with strict health protocols. Currently, the condition of the public open space at UPN